Characteristics of Multimodal Brain Connectomics in Patients With Schizophrenia and the Unaffected First-Degree Relatives - Lin, Xiao; Li, WeiKai; Dong, Guangheng; Wang, Qiandong; Sun, Hongqiang; Shi, Jie; Fan, Yong; Li, Peng; Lu, Lin (Frontiers in Cell and Developmental Biology, 2021)
Objective: Increasing pieces of evidence suggest that abnormal brain connectivity plays an important role in the pathophysiology of schizophrenia. As an essential strategy in psychiatric neuroscience, the research of brain connectivity-based neuroimaging biomarkers has gained increasing attention. Most of previous studies focused on single modality of the brain connectomics. Multi-modal evidence will not only depict the full profile of brain abnormalities of the patients, but also contribute to our understanding of the neurobiological mechanisms of this disease. Methods: In the current study, ninety-nine schizophrenia patients, sixty-nine sex- and education-matched healthy controls, and forty- two unaffected first-degree relatives of patients were recruited and scanned. The brain was parcellated into 246 regions and the multimodal network analyses were used to construct functional, anatomical, and morphological networks for each participant. Results: Using the brain connectomics from three modalities as the features, the multi-kernel support vector machine method yielded high discrimination accuracies for schizophrenia patients (94.86%) and for the first-degree relatives (95.33%), from healthy controls. Using an independent sample (49 patients and 122 healthy controls), we tested the model in an independent sample and achieved a classification accuracy of 64.57%. The convergent pattern within the basal ganglia and thalamus–cortex circuit exhibited high discriminative power during classification. Furthermore, substantial overlaps of the brain connectivity abnormality between patients and the unaffected first-degree relatives were observed, compared to healthy controls. Conclusions: The current findings demonstrate that decreased functional communications between the basal ganglia, thalamus, and the prefrontal cortex could serve as biomarkers and endophenotypes for schizophrenia.